Global impacts of U.S. bioenergy production and policy: a general equilibrium perspective - Evans, Samuel Garner, author; Hoag, Dana, advisor; Bond, Craig, committee member; Davies, Stephen, committee member; Paustian, Keith, committee member (Colorado State University. Libraries, 2012)
The conversion of biomass to energy represents a promising pathway forward in efforts to reduce fossil fuel use in the transportation and electricity sectors. In addition to potential benefits, such as greenhouse gas reductions and increased energy security, bioenergy production also presents a unique set of challenges. These challenges include tradeoffs between food and fuel production, distortions in energy markets, and terrestrial emissions associated with changing land-use patterns. Each of these challenges arises from market-mediated responses to bioenergy production, and are therefore largely economic in nature. This dissertation directly addresses these opportunities and challenges by evaluating the economic impacts of U.S. bioenergy production and policy, focusing on both existing and future biomass-to-energy pathways. The analysis approaches the issue from a global, economy-wide perspective, reflecting two important facts. First, that large-scale bioenergy production connects multiple sectors of the economy due to the use of agricultural land resources for biomass production, and competition with fossil fuels in energy markets. Second, markets for both agricultural and energy commodities are highly integrated globally, causing domestic policies to have international effects. The reader can think of this work as being comprised of three parts. Part I provides context through an extensive review of the literature on the market-mediated effects of conventional biofuel production (Chapter 2) and develops a general equilibrium modeling framework for assessing the extent to which these phenomenon present a challenge for future bioenergy pathways (Chapter 3). Part II (Chapter 4) explores the economic impacts of the lignocellulosic biofuel production targets set in the U.S. Renewable Fuel Standard on global agricultural and energy commodity markets. Part III (Chapter 5) extends the analysis to consider potential inefficiencies associated with policy-induced competition for biomass between the electricity and transportation fuel sectors.
Keywords: bioenergy; renewable fuel standard; general equilibrium